2012
DOI: 10.3168/jds.2011-4698
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intramammary infection on milk electrical conductivity in Murciano-Granadina goats

Abstract: Measurements of electrical conductivity (EC) of milk are used in mastitis detection in cows due to the low cost, possibility of automation, and rapid diagnosis, but the literature about EC measurement in goats is scarce. In this study, we studied the effect of the establishment of intramammary infection (IMI) on EC of goat milk by gland using daily measurements. Additionally, the effects on milk yield, somatic cell count (SCC), and mineral content were analyzed. Eight primiparous and 10 multiparous Murciano-Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
27
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 24 publications
(34 reference statements)
7
27
2
1
Order By: Relevance
“…This is probably due to the lack of a significant decrease of MY in non-healthy glands, also worsened by an insignificant correlation between deviations of MY and HS, which affected the accuracy of the model. These results seem to confirm that MY is not a useful parameter to detect HS in dairy goats, as found by Díaz et al (2012). However, in dairy cows the decrease of MY is generally more significant in cows with mastitis.…”
Section: Detection Characteristics Of Electrical Conductivity With Fusupporting
confidence: 71%
See 3 more Smart Citations
“…This is probably due to the lack of a significant decrease of MY in non-healthy glands, also worsened by an insignificant correlation between deviations of MY and HS, which affected the accuracy of the model. These results seem to confirm that MY is not a useful parameter to detect HS in dairy goats, as found by Díaz et al (2012). However, in dairy cows the decrease of MY is generally more significant in cows with mastitis.…”
Section: Detection Characteristics Of Electrical Conductivity With Fusupporting
confidence: 71%
“…However, in this study a higher prevalence of bilateral infections was observed (47.9 vs 32.3%). Díaz et al (2012) found a significant increase of EC only in cases of bilateral infection. Higher prevalence of bilateral infections observed in this study could therefore explain the different significance that data showed in terms of the relationship between EC and HS.…”
Section: Experimental Data Evaluationmentioning
confidence: 88%
See 2 more Smart Citations
“…There are several factors other than mastitis related to EC, including differences between animals, so that, in dairy cows, methods that employ an absolute EC threshold for all the animals for mastitis detection are not accepted, even if EC is measured in the complete milking or at gland level. Studies in dairy goats (Ying et al 2002;Diaz et al, 2011Diaz et al, , 2012Romero et al 2012) have shown significant effects of parity, lactation stage, farm, and the analyzed fraction, in addition to mammary infection.…”
Section: Introductionmentioning
confidence: 99%